A história da música sertaneja contada pelo fantástico: uma análise do bem sertanejo - Almeida, Adrielly Campos e (2018)
Bem Sertanejo is an attraction of the tv show “Fantástico” that proposes to tell the history of Brazilian country music. Michel Teló is the presenter of the series and invites the public to embark, along with him, on a journey that will retrace the path traveled by the genre, from its origins to the present day, trying to understand how the Brazilian country music is renewed. For this, he gathered, in environments of their respective daily lives, a group of Brazilian country music singers representing different times and talked with them about their life trajectories going through the history of the country music. The conversations were stitched together by information presented by Teló and the journalists of Fantástico, complemented by archive images. This research aimed to navigate this trip, in order to observe and analyze how the history of Brazilian country music is currently told through the series. In the baggage, as a source of information and object of comparison, were the itineraries left by the scholars who have already traveled along this path, and the theoretical contribution of Cultural Studies, which helped to understand better the cultural relations that permeate the genre. At the end of the investigation, through a content analysis, it was possible to infer that Bem Sertanejo followed different paths from those that had been traced by traditional authors like Waldenyr Caldas (1977, 1987) and Rosa Nepomuceno (1999) and approximated to what was traced by Gustavo Alonso (2011, 2015a), but without, however, problematizing the conflicts that involve the genre and its representatives. Thus the story of country music told by the series exhibits a sense of linearity and continuity between the representatives and especially between the idea of tradition and modernity that does not fully reflect the historical reality of the genre but helps to reframe it. It is also in line with popular and mass cultural understandings proposed by Cultural Studies, valuing popular practices as ways of life and, perceiving cultural consumption as a relation of recognition and mediation, as highlighted by Martín-Barbero (1997) and García -Canclini (2011, 1995).